2017
DOI: 10.2134/jeq2016.08.0294
|View full text |Cite
|
Sign up to set email alerts
|

Use of δ15N and δ18O Values for Nitrate Source Identification under Irrigated Crops: A Cautionary Vadose Zone Tale

Abstract: Source nitrogen (N) identification of leachate or groundwater nitrate is complicated by N source mixing and N and oxygen (O) isotope fractionation caused by microbial N transformations. This experiment examined the δN and δO values in leachate collected over 1 yr at 55 cm below raspberry ( L.) plots receiving either synthetic fertilizer (FT) or poultry manure (MT). The large ranges of δN (FT: -2.4 to +8.7‰, MT: +1.6 to +9.6‰) and δO (FT: -9.9 to -0.3‰, MT: -10.9 to +1.7‰) values in leachate collected under cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Shallow phreatic aquifers showed strongly dampened seasonal nitrate and isotopic variability compared to river waters. Given NO 3 − concentrations are generally buffered in aquifers over longer timeframes (e.g., years), the range of δ 15 N values in groundwater reflect longer-term climatic and land-use changes or established processes taking place in the soil and the unsaturated zone before NO 3 − leaches into the groundwater system 30,61 . The lack of a clear seasonal variation of δ 15 N and δ 18 O of NO 3 − in groundwater is attributed to nitrifying and mixing of nitrate sources introduced at different points or periods in time due to variable residence times (from months to years) in the unsaturated zone 38,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Shallow phreatic aquifers showed strongly dampened seasonal nitrate and isotopic variability compared to river waters. Given NO 3 − concentrations are generally buffered in aquifers over longer timeframes (e.g., years), the range of δ 15 N values in groundwater reflect longer-term climatic and land-use changes or established processes taking place in the soil and the unsaturated zone before NO 3 − leaches into the groundwater system 30,61 . The lack of a clear seasonal variation of δ 15 N and δ 18 O of NO 3 − in groundwater is attributed to nitrifying and mixing of nitrate sources introduced at different points or periods in time due to variable residence times (from months to years) in the unsaturated zone 38,62 .…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by measuring leachate under the raspberry row and alley using PCAPS over a 4-yr period including the establishment year (April 2009 to March 2010) and three cropping years (April 2010 to March 2013). Leachate NO 3 concentration and NO 3 isotope composition for two treatments on selected sampling dates over a 1-yr period from this study have been previously reported (Loo et al, 2017).…”
Section: Core Ideasmentioning
confidence: 97%
“…In this complex watershed including soil, farmland, wetlands and riverine transformations of N, the biological processes driving N cycling were deemed sufficient to initiate significant isotopic fractionation (Denk et al, 2017;Yu et al, 2020). Thus, we incorporated 15 N-fractionation factors for atmospheric deposition nitrate (0‰), nitrogen fertilizer (3.9 ± 2.3‰), soil nitrogen (− 4.1 ± 1.4‰) and municipal sewage (− 0.6 ± 1.2‰) during the SIAR modeling process (Ostrom et al, 1998;Loo et al, 2017;Zhang et al, 2018;Ren et al, 2022).…”
Section: Estimation Of Proportional Contributions From Potential Nitr...mentioning
confidence: 99%